The Incidence and Management Trends of Metastatic Spinal Tumors in South Korea: A Nationwide Population-based Study. Issue 14 (15th July 2020) - Choi, Sung Hoon; Koo, Ja Wook; Choe, DaeHyun; Kang, Chang-Nam
Abstract : Study Design: Population-based study. From 2008 to 2017, data from the national database of the Korean Health Insurance Review & Assessment Service were analyzed. The national insurance system and all medical expense bill data of the entire population are included in the database. Objective: The aim of this study was to elucidate the incidence and management trends of metastatic spinal tumors in South Korea. Summary of Background Data: The spine is the most common location of bone metastases. However, population-based studies in this topic are limited. Methods: The International Classification of Disease, 10th revision, medical behavior, and examination codes were used to identify the incidence and management trends of metastatic spinal tumors. The Cochran-Armitage trend test was used in statistical analysis. Results: Overall, 38, 007 patients (average age, 61 years) diagnosed with metastatic spinal tumors were analyzed. Metastatic tumors were most common in patients in their 60s (25.7%). The 10-year incidence of spinal metastases in South Korea was 6.68 cases per 100, 000 population. The age-adjusted incidence per 100, 000 population decreased from 8.16 cases in 2008 to 6.18 in 2017 ( P  = 0.03). Sex-adjusted incidence rates in men increased from 8.60 per 100, 000 persons in 2008 to 8.70 in 2017 ( P  < 0.001); those of women decreased from 8.20 per 100, 000 persons in 2008 to 4.15 in 2017 ( P  < 0.05). The most common primary tumor site was the lung (26.9%), followed by the breast (16.9%), prostate (10.8%), and liver (8.1%). Radiation therapy was constant at about 3500 cases per annum ( P  = 0.62); surgical treatment increased from 1158 to 1382 cases ( P  < 0.001). Resection and instrumentation surgeries increased significantly ( P  < 0.001), whereas cementation decreased continuously. Total healthcare costs increased significantly from $19, 925, 296 in 2008 to $30, 268, 217 in 2017 ( P  < 0.001). Conclusion: The incidence of metastatic spinal tumors decreased in South Korea. Resection and instrumentation procedures increased, and total healthcare costs increased rapidly. Level of Evidence: 3 Abstract : Based on the data from Korean Health Insurance Review & Assessment Service, the incidence of metastatic spinal tumors decreased in South Korea. Resection and instrumentation procedures increased and healthcare costs increased. The direction of surgical treatment is shifting from palliative treatment to identifying the current status and prognosis of patients.